Çocuk dostu sokak altyapısının değerlendirilmesi: Kocaeli -Yavuz Sultan Selim Mahallesi örneği - Tavlı, Dilay (Gebze Teknik Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2025)
Accessible, safe, and stimulating urban environments enhance children's freedom of movement while facilitating the daily lives of parents. The physical quality, functionality, and accessibility of streets play a crucial role in shaping the quality of children's relationship with the city, which in turn is of great importance in terms of urban social inclusion. The literature frequently emphasizes that children's interaction with the urban environment is directly linked to the physical characteristics and arrangements of the built environment.Studies on child-friendly cities and street design often fail to consider temporal variations and are generally limited in addressing the specific spatial needs of children aged 0–6. Internationally, the Bernard van Leer Foundation's Urban95 initiative and the (GDCI) Designing Streets for Kids guide are among the key resources that define principles of childfriendly urban design. While most studies focus on general design principles, the literature in Turkey tends to concentrate on subtopics such as open spaces, playgrounds, and traffic safety. However, a comprehensive methodological approach to evaluate street infrastructure and children's street experiences, specifically for the 0–6 age group, remains largely absent. In this context, the initial phase of this study discusses the significance of childfriendly cities and street design for young children. The second and third phases elaborate on the core concepts related to the topic and examine the importance of child-friendly streets; fundamental design criteria for neighborhood-level street infrastructure assessment are identified through an extensive literature review. In the fourth phase, the (AHP) method was employed to determine the relative importance of the selected criteria based on expert opinions. For the field study, Yavuz Sultan Selim Neighborhood in the Körfez district of Kocaeli province a densely populated and developing area with a high child population was selected as the research site. Using the grid analysis method, the neighborhood's pedestrian crossings, sidewalks, rest and play areas, seating elements, play and learning opportunities, nature and landscape arrangements, public transportation stops, bicycle infrastructure, bike lanes, and additional urban elements (e.g., fountains, street furniture) were evaluated in accordance with the identified criteria and sub-criteria. Streets and avenues that met these criteria were identified at the neighborhood scale. Incorporating the weighted significance of each criterion determined by experts, the study implemented a two-stage evaluation process to assess the extent to which the neighborhood's street infrastructure qualifies as child-friendly.In the final section, based on the findings obtained through the field study, the strengths and deficiencies of the street infrastructure in Yavuz Sultan Selim Neighborhood were identified in terms of child-friendly street design criteria, and suggestions were developed to address existing gaps. This study presents an original method for evaluating child-friendly street infrastructure at the neighborhood level. By assessing the compatibility of streets with established criteria through fieldwork, it proposes a practical model for local governments and related professional disciplines and aims to contribute to the development of child-friendly streets at the neighborhood scale. Keywords: Child-Friendly Urban Design, Child-Friendly Cities, Child-Friendly Streets, Early Childhood and Public Space, Urban Infrastructure for Children, Child-Friendly Street Infrastructure.

Erişilebilir, güvenli ve teşvik edici kentsel alanlar, çocukların hareket özgürlüğünü artırmakta ve ebeveynlerin günlük yaşamını kolaylaştırmaktadır. Sokakların fiziksel niteliği, işlevselliği ve erişilebilirliği, çocukların kentle kurduğu ilişkinin kalitesini belirlemekte; bu durum, kentlerin sosyal kapsayıcılığı açısından da önem taşımaktadır. Literatürde, çocukların kentsel çevreyle kurduğu ilişkinin fiziksel çevre düzenlemeleriyle doğrudan bağlantılı olduğu sıkça vurgulanmaktadır.Çocuk dostu kent ve sokak tasarımı üzerine çalışmalar, çoğunlukla dönemsel farklılıkları gözetmeden ele alınmakta; özellikle 0-6 yaş arası çocukların mekânsal ihtiyaçlarına odaklanan araştırmalar sınırlı kalmaktadır. Uluslararası alanda, Bernard Van Leer Vakfı'nın Kent95 girişimi ve Global Designing Cities Initiative (GDCI) tarafından hazırlanan "Çocuklar İçin Sokaklar Tasarlamak" rehberi, çocuk dostu kentsel tasarım ilkelerini belirleyen önemli kaynaklar arasındadır. Çoğu çalışma genel ilkelere odaklanırken, Türkiye'deki literatür genellikle açık alanlar, oyun alanları ve trafik güvenliği gibi alt başlıklara yoğunlaşmakta olup, 0-6 yaş grubu çocukların sokak deneyimleri ve altyapısının değerlendirilmesine yönelik kapsamlı bir metodolojik yaklaşım eksiktir. Bu bağlamda, çalışmanın ilk aşamasında çocuk dostu kentler ve sokak tasarımının çocuklar için öneminden bahsedilmiştir. Çalışmanın ikinci ve üçüncü aşamalarında, konuya ilişkin temel kavramlar ile çocuk dostu sokakların önemi ele alınmış; sokak altyapısının değerlendirilmesine yönelik literatür taranarak mahalle ölçeğinde temel tasarım kriterleri belirlenmiştir. Çalışmanın dördüncü kısmında temel alınan kriterlerin önem ağırlıklarını belirlemek için Analitik Hiyerarşi Süreci (AHP) yöntemi kullanılarak uzman görüşlerine başvurulmuştur. Alan çalışmasında ise, çocuk nüfusunun fazla ve konut yapısının yoğun ve gelişmekte olduğu bir bölge olarak Kocaeli ili Körfez ilçesi Yavuz Sultan Selim Mahallesi seçilmiştir. Mahalledeki yaya geçitleri, kaldırımlar, mola ve oyun alanları, oturma yerleri, oyun ve öğrenme, doğa ve peyzaj düzenlemeleri, toplu taşıma durakları, bisiklet altyapısı, bisiklet yolları, ek öğeler (çeşme, kent mobilyaları vb.) belirlenen kriterler ve alt kriterleri bağlamında grid analizi yöntemi yardımıyla mahalle ölçeğinde çocuk dostu sokak altyapısı değerlendirilmiş, alanda bu kriterleri karşılayan sokak ve caddeler belirlenmiştir. Uzmanlar tarafından tespit edilen niteliklerdeki ağırlıklarda çalışmaya dâhil edilerek, tüm mahalledeki sokak altyapısının çocuk dostu olup olmadığı iki aşamalı bir değerlendirme sürecinden geçirilmiştir. Çalışmanın son bölümünde, alan çalışması sonucu elde edilen bulgular ışığında, Yavuz Sultan Selim Mahallesi'ndeki sokak altyapısının çocuk dostu tasarım kriterlerine göre güçlü ve eksik yönleri belirlenmiş, eksikliklerin giderilmesine yönelik öneriler geliştirilmiştir. Bu çalışma, mahalle düzeyinde çocuk dostu sokak altyapısının değerlendirilmesine yönelik özgün bir yöntem sunmakta; alan çalışmasıyla sokakların belirlenen kriterlere uygunluk düzeyini ortaya koyarak, yerel yönetimler ve ilgili meslek disiplinlerine çocuk dostu kent tasarımları konusunda uygulanabilir bir model önermekte ve mahalle ölçeğinde çocuk dostu sokakların geliştirilmesine katkı sağlamayı amaçlamaktadır. Anahtar Kelimeler: Çocuk Dostu Kentsel Tasarım, Çocuk Dostu Kentler, Çocuk Dostu Sokaklar, Erken Çocukluk Dönemi ve Kamusal Alan, Çocuklar için Kentsel Altyapı, Çocuk Dostu Sokak Altyapısı
Evaluation of child friendly street infrastructure: The case of kocaeli-yavuz sultan selim neighborhood
Keywords: Şehircilik ve Bölge Planlama; Urban and Regional Planning